Effect of raw material variability of glipizide on the in vitro dissolution rate and in vivo bioavailability performance: The importance of particle size - Chenyao Zhao; Chan Jin; Hailing Gao; Liyuan Wang; Hongzhuo Liu; Zhonggui He (Elsevier, 2019)
The objective of this study was to understand the impact of active pharmaceutical ingredients (API) particle size on a re-developed generic product of glipizide and to improve its formulation so that it exhibits bioequivalent to that of the reference listed drug (RLD). Two commercial batches of APIs (API-1 and API-2) with the same polymorphism and one batch of home-made APIs (API-3) with super-small particle size were used in the present study. The in vitro dissolution profiles of the tested formulations were compared with the RLD in a series of dissolution media. Then, the impact of particle size on in vivo absorption was evaluated in Beagle dogs. Compared with the RLD, formulation A with larger API size showed slower dissolution in pH 6.0 and 7.4 medium, resulting bioinequivalent with the RLD. Conversely, formulation B with smaller API size demonstrated similar in vitro dissolution profiles with the RLD and thus exhibited bioequivalent in the present study. Furthermore, formulation C with super small particle size still exhibited identical oral absorption although rapid dissolution was observed in the tested condition. Herein, it indicated that 2-5 µm might be defined as the "inert size range" of glipizide for ensuring the bioequivalence with the RLD. The results in the present study might help to obtain a better understanding of the variability in raw materials for oral absorption, develop a bioequivalent product and thus post-market quality control. Keywords: Glipizide, Particle size, Product quality, Bioequivalence study, Dissolution